Reasons for individual ownership in Islamic law (Journal of the College of Basic Education, 2024)
Every Muslim has the right to property; Because it is a condition for the continuation of this worldly life, which is a road to the afterlife. He has the right to own a piece of land and build a house to shelter him, and he has the right to furnish it with what he deems comfortable. He has the right to buy food, drink, and clothing with the money he has, and he has the right to acquire a book, and organizing ownership means organizing the conduct of business. life; Because it is a regulation of one of the human instincts, which is the instinct of the love of possession and ownership. The property system means specifically the system of money, which is the backbone of life, as it is - in general, a determination of the extent of the competence of each member of society over the financial values that fall under his control and his exploitation of them through use and to what extent. The burdens placed on him and the controls imposed on him related to this control and required by the public interest. The topic included three topics. In the first topic, I explained individual ownership, its function, and types. In the second topic, I explained the reasons for ownership among Islamic sects and its controls. In the third topic, I explained the scope of ownership. Individuality and its limits.